The composition of Algerian society between diversity and conflict - CHETTOUH, Ahmed abdelatif (Social Sciences Journal)
In Algeria today the side of events occupies a big degree of tension and conflict between groups from one side and the political system in another side.Whereas it is necessary to achieve unity and integration through the conversion of a pluralistic society to a culturally homogeneous society based on diversity and harmony as a requirement is necessary. It becomes important to look for mechanisms of this transformation, and this what we will show in that study